Source and formation process impact the chemodiversity of rainwater dissolved organic matter along the Yangtze River Basin in summer. (1st March 2022) - Chen, Shuang; Xie, Qiaorong; Su, Sihui; Wu, Libin; Zhong, Shujun; Zhang, Zhimin; Ma, Chao; Qi, Yulin; Hu, Wei; Deng, Junjun; Ren, Lujie; Zhu, Dongqiang; et al.
Highlights: Rainwater DOM along the yangtze river were characterized by optical properties and FT-ICR MS. Natural and anthropogenic emissions and climatic conditions shaped the chemodiversity of rainwater DOM. Biogenic secondary organic compounds widely contributed to rainwater DOM along the Yangtze River Basin. Abstract: Rainwater dissolved organic matter (DOM) plays an important role in the biogeochemical cycle and evolution of organic matter in the land-atmosphere interface. To better understand their sources and molecular composition in the atmosphere, rainwater samples were collected at six different locations along the Yangtze River Basin. Based on the application of a combined approach including excitation-emission matrix (EEM) fluorescence and Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS), various sources (terrestrial, anthropogenic, and autochthonous sources) of rainwater DOM were revealed. Results show that the derivatives of biogenic volatile organic compounds were widely distributed and contributed to rainwater DOM along the Yangtze River Basin. In the up-river city Batang, rainwater DOM was affected by the long-range atmospheric transport due to the Indian summer monsoon. Lijiang, a city on the southeastern edge of Tibetan plateau, was related to strong local biomass burning. The industrial cities of Panzhihua and Luzhou showed large differences in organic composition due to distinct industrial types. Fuling, a district in Chongqing Municipality, was significantly contributed by aged organics from biomass burning. While rainwater DOM in Shanghai, a coastal megacity, contained a high fraction of sea spray organics. Further, more than 70% of rainwater DOM molecules are associated with 36 typical transformation mechanisms during rainwater-scavenging processes, e.g., oxidation reactions, dealkylation and decarboxylation. Our study demonstrates that local natural and anthropogenic emissions and climatic conditions strongly shaped the chemodiversity and possible precursor-product pairs of rainwater DOM along the Yangtze River Basin, which helps to better understand the biogeochemical cycles of organic matter in a large-scale watershed under the influence of human activities. Abstract : Image, graphical abstract